Política de Educação Integral: Avaliação do Programa Mais Educação e Concepções de Educação Integral na Escola Municipal de Educação Infantil e Ensino Fundamental Professora Fernanda Maria de Alencar Colares - Garcia, Solange Maria Colares (2013)
The goal of this dissertation is to assess the implementation of the Program More Education (PME) on Municipal School of early childhood education and elementary school Municipal Fortaleza by means of conceptions of integral education, the actions of the program and the results seen by the social actors involved in the PME, of the Municipal Secretary of Education (SME), the Regional Executive Secretariat (SER-VI). To this end, we held a discussion on "in-depth review", in which we seek theoretical on Silva, who discusses evaluation of results, and in Rodrigues, who comes to in-depth assessment and highlighting aspects which guided the research, such as: institutional material analysis in the form of law, ordinances, documents, statistical and other data; analysis of the context of the formulation of policy with the construction of the political career of politics of integral education in Brazil; and the institutional history of PME, specifically in Fortaleza. Finally, we performed a case study where we use a number of techniques and instruments, such as participant observation, interviews and the focus group. In data collection, face the conceptions about PME, representatives of PME, SER-VI and the school with the following actors: management, Coordinator of the PME, pedagogical coordinators, teachers, parents and students. Finally, in the analysis, face these conceptions with the theoretical work sustainability that when we present three theoretical assumptions: the first deals with the integral education in the perspective of the human being in its entirety, rather than the idea of expanding the school day; the second discusses integral education as a right and with a view to full protection; and the third discusses integral education as a means to bring the man to the construction of the autonomy and emancipation, that is, confronting the logic of capital under neo-liberal policies. Soon, our evaluative research trajectory, we note several conceptions of integral education, such as: integral education as a possibility to ensure protection to students and integral education full-time as a right which should be offered as an instrument to ensure the full development through access to cultural assets, so that they, in turn, enable its completeness. Finally, we will work to design integral education, which sees the PME and the school as the Redeemer and the instrument to solve social problems such as violence and involvement with drugs. In the survey, other dimensions evaluated were the actions and results of the implementation of PME in school, the point from which we find that the results according to the understanding of the actors involved are positive. This happens since the managers, teachers and coordinators, which justify and explain the importance of PME and the opportunities for students to have access to cultural goods which, otherwise, would not. Parents understand the program as a space in which they can leave their children so they can learn more and be safe and free from violence. Finally, students understand how a significant advance in their lives, both in and outside school. The conclusion we have reached is that there are several ways of thinking integral education and PME, primarily within the school, because, in our view, these various forms of thinking are other tones in the implementation of the PME. Why as the conceptions are different, the positions are. Therefore, regardless of the conceptions of each actor involved, everyone understands and advocate the importance of PME within the school as an instrument 10 that provides access to cultural goods to students and as a means of providing more opportunities which, otherwise, students would not have. Keywords: Conceptions of integral education. Evaluation of public policies. More Education Program.